Hydrothermal processing of laminaria ochroleuca for the production of crude extracts used to formulate polymeric nanoparticles - Flórez-Fernández, Noelia (2020)
A green extraction process using only water was proposed for the simultaneous extraction of alginate and bioactive compounds from Laminaria ochroleuca. Operation was carried out during non-isothermal heating up to maximal temperatures over the range of 70 °C to 100 °C. Once separated, the alginate and the crude extract were characterised and the biological activities and cytotoxicity of the extracts was studied, the latter in intestinal epithelial cells. Those alginates obtained at 90 °C exhibited the highest extraction yields and viscoelastic features of the corresponding hydrogels. The obtained results show that the extracts obtained by non-isothermal extraction were suitable to formulate nanoparticles, which showed the smallest size (≈ 250-350 nm) when the higher content of fucoidan extract was present. Given the evidenced properties, the extracts may find an application in the formulation of nanoparticulate carriers for drug delivery.